Gaya Kepemimpinan Ibu Nyai dalam Mengembangkan Manajemen Pondok Pesantren Roudlotul Qur’an Kecamatan Balung Kabupaten Jember - Riski, Shona Amelia (Maddah: Journal of Advanced Da'wah Management Research, 2023)
A Nyai in an Islamic boarding school is a fairly central figure. Not only is the spiritual leader of the students, the mother is also responsible for overall life in the Islamic boarding school. This research aims to describe Nyai's leadership in developing Islamic boarding schools (case study at Roudlotul Qur'an Islamic boarding school) which includes the role and advantages and disadvantages of Mrs. Nyai's leadership style. In conducting research, the approach used by researchers is a qualitative approach, the type of which is descriptive. Observations, interviews and documentation were carried out by researchers to collect the data. Meanwhile, data collection, data reduction, data presentation, and drawing conclusions are the data analysis stages. In order to test the validity of the data, researchers triangulated sources and methods. The results of the research show that the caretaker of the Roudlotul Qur'an Islamic boarding school, Mrs. Hj. Mulazimatul Munawaroh belongs to the charismatic leadership style. The leadership role of the mother is divided into 2, namely the domestic leadership role and the public leadership role. As for the strengths and weaknesses, the researchers used a SWOT analysis, divided as follows: First, internal factors include strength and opportunity. Second, external factors include Weakness and Threat.